Towards a culturally responsive pedagogy of practice - Walkus, Jillian Jonelle (2014)
This project documents the exploration and incorporation of culturally responsive teaching and learning practices. Culturally responsive teaching uses the cultural characteristics, experiences and perspectives of ethnically diverse students as a means for effective teaching. The literature review explores the theoretical definition of culturally responsive pedagogy and identifies common principles in scholarly works. Literature selected to review includes culturally responsive education within Indigenous communities as a means to identify teacher practices that facilitate student learning through the validation of culture. Graduate